2017
DOI: 10.1080/13669877.2017.1359204
|View full text |Cite
|
Sign up to set email alerts
|

Ulrich Beck: exploring and contesting risk

Abstract: While risk research normally understands risk as an entity that can be calculated using statistics and probabilities-and which therefore also can become the object of insurance technology-it is the production of new, non-calculable risks and therefore also risks that cannot be insured against, which is at the centre of Ulrich Beck's risk society theory. The article examines Beck's conceptualization of risk and discusses how he has clarified and further refined the concept since publishing Risk Society in 1986.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
11
0
5
Order By: Relevance
“…Our study found that the public blamed not only individuals who put others at greater risk during the epidemic but also government, particularly local government figures for their perceived failures in risk communication and control measures. This also aligns with Beck's works on global risk society, in which authorities are increasingly questioned and blamed for failing to protect individuals [54]. Current data reveals seldom use of conspiracy theories in the attribution of blame and blame as a way to spread rumors [55].…”
Section: Principal Findingssupporting
confidence: 71%
“…Our study found that the public blamed not only individuals who put others at greater risk during the epidemic but also government, particularly local government figures for their perceived failures in risk communication and control measures. This also aligns with Beck's works on global risk society, in which authorities are increasingly questioned and blamed for failing to protect individuals [54]. Current data reveals seldom use of conspiracy theories in the attribution of blame and blame as a way to spread rumors [55].…”
Section: Principal Findingssupporting
confidence: 71%
“…Comparable public debates arose around, for example biotechnology [4], electromagnetic fields [5] and food additives [6]. Public debates about these so called ‘modern risks’ are often characterised by concerns about invisible hazardous substances, and potential, though often highly uncertain, health consequences [7,8]. These public concerns about risks can have considerable societal impact.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, it has been translated into more than 35 languages (Mythen 2018). He connected institutional change and its daily micro-political challenges in fields such health, economy, and environment (Sørensen 2018). Environmental risks, Beck argues, promote important changes in society, especially air pollution and radioactive contamination.…”
Section: Risk Society and The New Modernitymentioning
confidence: 99%